EQTLHap: a tool for comprehensive eQTL analysis considering haplotypic and genotypic effects. Issue 5 (8th April 2021) - Al Bkhetan, Ziad; Chana, Gursharan; Soon Ong, Cheng; Goudey, Benjamin; Ramamohanarao, Kotagiri
Abstract: Motivation: The high accuracy of recent haplotype phasing tools is enabling the integration of haplotype (or phase) information more widely in genetic investigations. One such possibility is phase-aware expression quantitative trait loci (eQTL) analysis, where haplotype-based analysis has the potential to detect associations that may otherwise be missed by standard SNP-based approaches. Results: We present eQTLHap, a novel method to investigate associations between gene expression and genetic variants, considering their haplotypic and genotypic effect. Using multiple simulations based on real data, we demonstrate that phase-aware eQTL analysis significantly outperforms typical SNP-based methods when the causal genetic architecture involves multiple SNPs. We show that phase-aware eQTL analysis is robust to phasing errors, showing only a minor impact (<4% ) on sensitivity. Applying eQTLHap to real GEUVADIS and GTEx datasets detects numerous novel eQTLs undetected by a single-SNP approach, with 22 eQTLs replicating across studies or tissue types, highlighting the utility of phase-aware eQTL analysis. Availability and implementation: https://github.com/ziadbkh/eQTLHap . Contact: ziad.albkhetan@gmail.com Supplementary information: Supplementary data are available at Briefings in Bioinformatics online.